Impacts of different land management histories on forest change. Issue 8 (17th November 2017) - Collins, Brandon M.; Fry, Danny L.; Lydersen, Jamie M.; Everett, Richard; Stephens, Scott L.
Abstract: Many western North American forest types have experienced considerable changes in ecosystem structure, composition, and function as a result of both fire exclusion and timber harvesting. These two influences co‐occurred over a large portion of dry forests, making it difficult to know the strength of either one on its own or the potential for an interaction between the two. In this study, we used contemporary remeasurements of a systematic historical forest inventory to investigate forest change in the Sierra Nevada. The historical data opportunistically spanned a significant land management agency boundary, which protected part of the inventory area from timber harvesting. This allowed for a robust comparison of forest change between logged and unlogged areas. In addition, we assessed the effects of recent management activities aimed at forest restoration relative to the same areas historically, and to other areas without recent management. Based on analyses of 22, 007 trees (historical, 9, 573; contemporary, 12, 434), live basal area and tree density significantly increased from 1911 to the early 2000s in both logged and unlogged areas. Both shrub cover and the proportion of live basal area occupied by pine species declined from 1911 to the early 2000s in both areas, but statistical significance was inconsistent. The most notable difference between logged and unlogged areas was in the density of large trees, which declined significantly in logged areas, but was unchanged in unlogged areas. Recent management activities had a varied impact on the forest structure and composition variables analyzed. In general, areas with no recent management activities experienced the greatest change from 1911 to the early 2000s. If approximating historical forest conditions is a land management goal the documented changes in forest structure and composition from 1911 to the early 2000s indicate that active restoration, including fire use and mechanical thinning, is needed in many areas.